To make people save energy tell them what others do but also who they are: a preliminary study - Graffeo, Michele; Ritov, Ilana; Bonini, Nicolao; Hadjichristidis, Constantinos (Frontiers in Psychology, 2015)
A way to make people save energy is by informing them that “comparable others” save more. We investigated whether one can further improve this nudge by manipulating Who the “comparable others” are. We asked participants to imagine receiving feedback stating that their energy consumption exceeded that of “comparable others” by 10%. We varied Who the “comparable others” were in a 2 × 2 design: they were a household that was located either in the same neighborhood as themselves or in a different neighborhood, and its members were either identified (by names and a photograph) or unidentified. We also included two control conditions: one where no feedback was provided, and one where only statistical feedback was provided (feedback about an average household). We found that it matters Who the “comparable others” are. The most effective feedback was when the referent household was from the same neighborhood as the individual’s and its members were not identified.